Impact of photoreceptor density in a 3D simulation of panretinal laser photocoagulation - Nishida, Kentaro (BMC Ophthalmol, 2021)
BACKGROUND: During panretinal photocoagulation (PRP), the outer retina, especially the photoreceptors, are destroyed. During such procedures, the impact of the retinal photocoagulation, which is performed in the same photocoagulated area, may change if it is applied to different locations with different photoreceptor densities. Thus, we aimed to evaluate the influence of photoreceptor density on PRP. METHODS: We constructed a three-dimensional (3D) average distribution of photoreceptors with 3D computer-aided design (CAD) software using previously derived photoreceptor density data and calculated the number of photoreceptors destroyed by scatter PRP and full-scatter PRP (size 400-μm on the retina, spacing 1.0 spot) using a geometry-based simulation. To investigate the impact of photoreceptor density on PRP, we calculated the ratio of the number of photoreceptors destroyed to the total number of photoreceptors, termed the photoreceptor destruction index. RESULTS: In this 3D simulation, the total number of photoreceptors was 96,571,900. The total number of photoreceptors destroyed by scatter PRP and full-scatter PRP were 15,608,200 and 19,120,600, respectively, and the respective photoreceptor destruction indexes were 16.2 and 19.8%, respectively. CONCLUSIONS: Scatter PRP is expected to have 4/5 of the number of photoreceptors destroyed by full-scatter PRP. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12886-021-01945-z.